Art of Renaissance Venice: 1400 - 1600 - Partridge, Loren W. (Univ. of California Press, 2015)
"A comprehensive and richly illustrated survey of Venetian Renaissance architecture, sculpture, and painting created between 1400 and 1600 addressed to students, travellers, and the general public. The works of art are analysed within Venice's cultural circumstances--political, economic, intellectual, and religious--and in terms of function, style, iconography, patronage, classical sources, gender, art theories, and artist's innovations, rivalries, and social status. The text has been divided into two parts--the fifteenth century and the sixteenth century--each part preceded by an introduction that recounts the history of Venice to 1500 and to 1600 respectively, including the city's founding, ideology, territorial expansion, social classes, governmental structure, economy, and religion. The twenty-six chapters have been organized to lead readers systematically through the major artistic developments within the three principal categories of art--governmental, ecclesiastic, and domestic--and have been arranged sequentially as follows: civic architecture and urbanism, churches, church decoration (ducal tombs and altarpieces), refectories and refectory decoration (section two only), confraternities (architecture and decoration), palaces, palace decoration (devotional works, portraits, secular painting, and halls of state), villas, and villa decoration. The conclusion offers an overview of the major types of Venetian art and architectural patronage and their funding sources"--Provided by publisher